الكونيات في الدرس العقدي المعاصر عند محمد سعيد رمضان البوطي - طريلي العطرة (University of Eloued جامعة الوادي, 2024)
"يتناول هذا البحث موضوع الكونيات عند علم من أعالم الدعوة اإلسالمية المعاصرة وهو الشيخ محمد سعيد رمضان البوطي، حيث عالجت فيه مبحث الكونيات كما تناولها المؤلف في كتابه كبرى اليقينيات الكونية وكتبه األخرى للحقائق للمفاهيم وبياناً تحديدا . وقد اعتمدت في هذا البحث على المنهج االستقرائي ً بالوقوف على الكونيات في كتب الشيخ البوطي، كذلك المنهج الوصفي الذي و ّظفته في عرض فكر ورؤية محمد سعيد رمضان البوطي للكونيات، باإلضافة إلى التحليل لفهم نصوصه وعباراته. ومن نتائج هذا البحث: يعد محمد سعيد رمضان البوطي شخصية معاصرة ظهرت في مناخ فكري متالطم األمواج عالج العديد من القضايا أبرزها مبحث الكونيات الذي يتمحور من خالله عدة محاور من بينها اإلنسان والمالئكة والجان والسنن الكونية وتعتبر هذه المحاور ردا على الرؤية المادية والفلسفات الغربية.""This research deals with the subject of the cosmology as discussed by one of the prominent contemporary figures in Islamic preaching, Sheikh Mohammad Saeed Ramadan Al-Bouti. Where, I dealt with the subject of cosmological themes as the author in his work ""Major Cosmic Convictions"" and other writings, specifically elucidating concepts and presenting truths. In this research, I relied on the inductive approach by examining Sheikh Al-Bouti's cosmological perspectives found in his books, alongside a descriptive methodology to present and analyze his cosmological ideas, including textual interpretations and expressions. Among the findings of this research is that Mohammad Saeed Ramadan Al-Bouti emerges as a contemporary figure that appeared amidst a tumultuous intellectual environment, addressing various issues prominently including cosmological themes. These themes revolve around several axes such as humans, angels, jinn, and cosmic norms, collectively serving as responses to materialistic viewpoints and Western philosophies."
Keywords: الكونيات- الدرس العقيدي -محمد سعيد البوطي; Universalities - The Doctrinal Lesson - Muhammad Saeed Al-Bouti